The FABP4 gene polymorphism is associated with meat tenderness in three Chinese native sheep breeds - Q.L. Xu; G.W. Tang; Q.L. Zhang; Y.K. Huang; Y.X. Liu; K. Quan; K.Y. Zhu; C.X. Zhang (Czech Journal of Animal Science, 2011)
The aim of this study was to assess the association of single nucleotide polymorphisms (SNP) of sheep fatty acid binding protein 4 (FABP4) gene with longissimus thoracis muscle (LT) meat quality traits in sheep. The FABP4 cDNA was cloned by RT-PCR method, and the sequence analysis showed that the open reading frame of sheep FABP4 is 399 bp and codes 132 amino acids. A mutation (A/G) detected in intron 1 of FABP4 gene was studied in 286 lambs of three Chinese native sheep breeds by PCR-SSCP procedure. Significant statistical association results revealed that AA genotype conferred higher tenderness (P < 0.05), muscle marbling score (P < 0.05) and intramuscular fat content (IMF; P < 0.05). Thus we suggested that the genotype AA could be regarded as a molecular marker for LT meat tenderness and IMF content in sheep.